Triathlon and ultra-endurance events in tropical environments - Chabert, C.; Hermand, E.; Hue, O. (Heat stress in sport and exercise. Thermophysiology of health and performance, 2019)
Physical performance in tropical environments, which combine heat and high humidity, is a challenge that requires specific preparation. The high humidity of a tropical climate alters thermoregulatory capacity by limiting the rate of sweat evaporation. Proper management of whole-body temperature is thus essential to complete an endurance event like a long-distance triathlon or an ultramarathon in such an environment. In triathlon and ultra-endurance races, which can last from 8 to 20 h, performance in tropical settings is closely linked to the capacity to maintain hydration status. Indeed, the rate of withdrawal in these longer events has been associated with water intake, with many finishers showing alterations in electrolyte (e.g., sodium) balance. To counterbalance the impact of a tropical climate and maintain performance, several countermeasures can be adopted, such as using hydration and cooling strategies, and heat acclimation.